Implant installation in patients with periodontal disease history (Research, Society and Development, 2020)
It is already established in the clinical routine of oral rehabilitation the inclusion of osseointegrated implants. The search for this type of treatment has become popular and, with it, maintenance problems should be well studied and treated by professionals in this area. It is unlikely that many of these patients who are candidates for implant treatment were not victims of any periodontal disease. In rehabilitation planning, in some situations, failures may occur soon after implant placement or later, when the implant is already osseointegrated. These failures are generally related to bacterial contamination both during surgery and subsequent colonization of these pathogens in the periimplant region. This article aims to conduct a survey of the current medical literature on the installation of implants in patients with a history of periodontal disease. As a methodology, Scopus, Web of Science and Google Scholar indexing portals were scanned with the terms implantodontics, periodontics and periodontal diseases. A total of 9,876 articles were found and 25 articles were selected considering the relevance or impact factor of the journals where these articles were published. It is concluded that there is a direct relationship between dental implant loss and periodontal disease.